Genesis of the Institute of Interaction of the State Border Guard Service of Ukraine with Other Law Enforcement Agencies - І. І. Baidyuk (Law and Safety)
The article is focused on the research of historical aspects of interaction between the State Border Service of Ukraine with other law enforcement agencies of Ukraine, which is conditioned by the importance of the tasks assigned to the State Border Service of Ukraine on the security and protection of the state borders, especially in the current conditions of integration of the state into the European space, by reforming a number of law enforcement agencies of Ukraine, the creation of new law enforcement structures and, accordingly, the need to improve existing or establish new cooperation mechanisms of interaction between the above entities. Both general scientific and special methods of scientific cognition made possible to achieveg the set goal and objectives of the study. The central method of the research was the historical and legal method, which allowed to reveal both the historical aspects and the legal basis of interaction of the State Border Service of Ukraine with other law enforcement agencies at different stages. The peculiarities of the interaction of the state border protection agencies with other state entities have been clarified since the V century, when the need for the protection of state borders was first realized and the relevant agencies were created. The author has determined law enforcement agencies that interact with the State Border Service of Ukraine nowadays and the legal basis of such interaction. Particular attention has been paid to the specifics of carrying out interaction of the State Border Service of Ukraine with other law enforcement agencies within the framework of the special border operation “Border”, as well as on the territory of the operation of the joint forces.